The leaf-miner (Leucoptera coffeella) incidence in coffee culture (Coffea arabica) under central pivot irrigation - Custódio, Anselmo Augusto de Paiva; Moraes, Jair Campos; Custódio, Adriano Augusto de Paiva; Lima, Luiz Antônio; Faria, Manoel Alves de; Gomes, Natalino Martins (Coffee Science - ISSN 1984-3909, 1970)
The leaf-miner (LM) [Leucoptera coffeella (Guérin-Menéville & Perrottet, 1842) (Lepidoptera: Lyonetiidae)] is one of the most powerful parasites for the coffee plants (Coffea arabica L.), being responsible for high economic losses to coffee farmers. In the last years, the adoption of irrigation systems has been becoming a common practice in Brazilian coffee farms, mainly center pivot irrigation. The principal factors that contribute to the increase of irrigated fields are the negative effects of bad rain distribution and hydric scarceness. However, there is data describing the behavior of this parasite in irrigated crops. The aim of this work was to verify the incidence of LM in a coffee fields submitted to a center pivot irrigation system with different water depths applied. The research was carried out in a experimental field with total area of 1,6 ha located in the Engineering Department of the Federal University of Lavras. The coffee trees susceptible to LM were planted in 1999, each plot with 3,5m x 0,8m of space between plants. The work was designed in randomized block model and treatments analyzed were 6 water depths applied (0, 60, 80, 100, 120 and 140% of evaporation of the class A tank - ECA) in different periods of evaluation, in a factorial scheme (6 x 12) with 3 repetitions. The LM infection in the plants was verified by visual evaluation of leaf damages caused by the parasite. The analyses were proceeded in intervals of 23 days, from April of 2004 to March of 2006. Each experimental group was composed of eight plants. Ten plagiotropics branchs were sampled in the medium part of tree, being five of the south and five of the north side of the plant. Two leaves located in the thrith or fourth pair of each branch was collected, in total of 160 leaves per experimental group. The mean dates of percentage of mined leaves were transformed using the formula (X + 0,5)1/2 and an analysis of variance was made. The results showed a significant interaction between water depths and LM incidence. The higher incidence of LM infection was observed in no irrigated plants. The experimental group submitted 140% ECA showed lower LM parasitism. The higher amount of the insects was observed in the north side of plants. Two peaks of LM incidence occurred, in January and July, with high number in the first.